Pengaruh Kualitas Produk, Persepsi Harga, dan Digital Marketing terhadap Keputusan Pembelian Produk Tas Lokal Merk Flicka Bags Pada Mahasiswa Universitas 17 Agustus 1945 Surabaya - Deby Annisah Prasuti; Ulfi Pristiana (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This study aims to prove and analyze the influence of product quality, price perception, and digital marketing on purchasing decisions for Flicka Bags products. This study uses a quantitative method with a questionnaire instrument. The sampling technique uses the Slovin formula size of 100 respondents The data analysis technique used was multiple regression analysis with the help of the SPSS version 30 program (statistical program for social science). While the tests used were Validity and Reliability Tests, Determination Coefficient Tests, and Hypothesis Tests both partially and simultaneously. This study states that the independent variables, namely product quality, price perception, and digital marketing have a positive and significant effect on the dependent variable of purchasing decisions. The result of the t-value is 2.946 > 1.98, so Ho is accepted and Ha is rejected, while the result of the determination coefficient test obtained an R value of 0.527, which means that the independent variables Product Quality (X1), Price Perception (X2), and Digital Marketing (X3) have an influential contribution to the dependent variable Purchase Decision (Y), this shows that 52.7% while the remaining 47.3% is in other variables outside the model studied.